Risk factors and clinical outcome of postoperative hyperglycemia after cardiac surgery with cardiopulmonary bypass - Xiang, Yuping; Luo, Tianhui; Zeng, Ling (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThere is a high incidence of postoperative hyperglycemia (PHG) in cardiac surgery with cardiopulmonary bypass (CPB), as well as increased morbidity and mortality. The purpose of this study was to evaluate the incidence of PHG after cardiac surgery with CPB, the independent risk factors, and its association with clinical outcomes.MethodsThis was a retrospective, observational study of patients who underwent cardiac surgery with CPB between January 2023 and March 2024 in West China Hospital of Sichuan University. A total of 1,008 consecutive postoperative cardiac surgery patients admitted to the cardiac surgery intensive care unit (ICU) were divided into a non-PHG group and a PHG group. Patients’ blood glucose levels were evaluated immediately after cardiac surgery and every 3–4 h daily for 10days, until discharge from the ICU. For patients with PHG, intravenous insulin infusion was performed according to the institution's protocol, and perioperative risk factors for hyperglycemia and clinical outcomes were assessed.ResultsPHG, defined as random blood glucose ≥10.0 mmol/L (180 mg/dl) on two occasions within 24 h, occurred in 65.28% of cardiac surgery patients. Multivariable logistic regression analysis identified that age [odds ratio (OR) 1.054, 95% confidence interval (CI) 1.040–1.069; p < 0.001], female sex (OR 1.380, 95% CI 1.023–1.864; p = 0.035), diabetes (OR 13.101, 95% CI 4.057–42.310; p < 0.001), pulmonary infection (OR 1.918, 95% CI 1.129–3.258; p = 0.016), aortic cross-clamp time (OR 1.007, 95% CI 1.003–1.010; p < 0.001), and intraoperative highest glucose (OR 1.515, 95% CI 1.370–1.675; p < 0.001) emerged as independent risk factors for PHG. Moreover, PHG had higher rates of acute kidney injury (12.61% vs. 4.00%; p < 0.001), delirium (9.57% vs. 3.43%; p < 0.001), pulmonary infection (12.01% vs. 5.14%; p < 0.001), longer duration of mechanical ventilation (19 vs. 14 h; p < 0.001), length of ICU stay (74 vs. 58 h; p < 0.001), length of hospitalization (13 vs. 11 days; p < 0.001), and higher rate of self-discharge or death (3.95% vs. 0.57%; p = 0.002) compared with patients with non-PHG.ConclusionsPHG occurs frequently in patients after cardiac surgery. Age, female, diabetes, pulmonary infection, aortic cross-clamp time, and intraoperative highest glucose were independent risk factors for PHG. PHG is associated with worse clinical outcomes, including a higher rate of acute kidney injury, delirium, and pulmonary infection, greater duration of mechanical ventilation, length of ICU stay, length of hospitalization, and higher rate of automatic discharge or death.